Dampak Model Pembelajaran Discovery Learning Dalam Pelajaran Instalasi Penerangan Listrik - Wahyu Rahma Irwan; Fivia Eliza (Jurnal Pendidikan Teknik Elektro, 2023)
Learning activities that take place at SMKN 5 Padang only use the lecture method. The lecture method causes students to feel bored quickly in learning. This also occurs due to the lack of activeness of educators in varying the methods used during learning as a result of which students get unsatisfactory grades. Therefore a discovery learning method is needed where the aim is to find out the impact of applying the discovery learning model at SMKN 5 Padang. This study aims to determine the impact of the discovery learning learning model at SMKN 5 Padang. in terms of student learning outcomes in the subject of Electrical Lighting Installation in class XI TITL. This type of research is a type of quantitative research using pre-experimental methods. The research design used was one group pretest-posttest with an experimental class and a control class. The research instrument was in the form of questions that had been tested beforehand to find out the validity, reliability, difficulty index of the questions and the differential power of the questions and then analyzed using Effect Size. This research was conducted in class XI TITL with 30 students as respondents and the results showed that learning using the discovery learning model in the Electrical Lighting Installation subject at SMK Negeri 5 Padang had a major impact or influence on student learning outcomes.